Building AC/DC microgrid design - Li, ChengJing (2017)
Electricity energy is the most fundamental element to promote the development of modern society. We need to use to it anytime and anywhere which is almost the basic necessaries in our daily life. However, most of the power source is non-renewable and have harmful by-products to the environment. For the moment, Singapore generate electricity that mostly come from natural gas which imported from other countries. So it is necessary to find some alternative source to keep a stable and sustainable development. Singapore does not have any natural resources while it has plenty of sunlight which is clean and reproducible. Thanks to the modern technology, we could convert the solar energy to electricity energy by the PV system. On the other hand, there are more and more electronic device using DC voltage while traditional power grid only provide AC voltage. So it will be convenient to provide both AC and DC power in one system. In this way, we could use the concept of Micro grid which is small scale power distribution network and integrate with renewable energy source and storage system. This project will be focused on the AC/DC micro-grid in the residential buildings. In order to design a suitable, reliable and cost-effective power system, I will need to calculate all the AC and DC loads of the building, then finalize the size of PV unit, inverter and batteries according to the loads and installation area in the rooftop. Based on the data obtained, the structure of system will be decided. And the overall cost of the project and payback period will be analysed and calculate. In the meantime, the simulation will be conducted in the Homer to evaluate and choose a most suitable solution to the fit the design. Through the project, we will know proportion of the power supply that micro-grid could provide for whole building loads and the estimated cost and payback period for the whole project.